Eosinophilic and lymphoplasmacytic enteritis in a horse - case report - R.C. Machado; C.F. Teixeira; H.D. Carvalho (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Among the Inflammatory Bowel Diseases in horses, eosinophilic and lymphoplasmacytic enteritis is rare and is characterized by an infiltrate of inflammatory cells, causing problems with nutrient absorption, diffuse neoformation and changes in the histological structure of all the tissue layers of the intestine. This report describes a case of eosinophilic and lymphoplasmacytic colitis in an 11-year-old male horse with progressive weight loss, sings of colic syndrome and apathy. No alterations were found in the blood Count, except for leukocytosis with neutrophilia. The biochemical examination showed an increase in indirect bilirubin, and the peritoneal fluid showed a high concentration of total protein, lactate and total nucleated cells. Ultrasound identified free fluid in the abdominal cavity and neoformation in the colon. In view of the findings, exploratory celiotomy was recommended; however, euthanasia was chosen considering the cost-benefit and zootechnical value of the animal. Post-mortem histopathological examination of fragments of the greater and lesser colon identified Lymphoplasmacytic colitis and eosinophilic colitis, chronic process, with no determined cause and treatment that is not always effective, but preventive health management measures minimize the triggering factors.